Tomography Imaging of Lithium Electrodeposits Using Neutron, Synchrotron X-Ray, and Laboratory X-Ray Sources: A Comparison - Magnier, Lucile; Lecarme, Lauréline; Alloin, Fannie; Maire, Eric; King, Andrew; Bouchet, Renaud; Tengattini, Alessandro; Devaux, Didier (Frontiers in Energy Research, 2021)
X-ray and neutron imaging are widely employed for battery materials thanks to the possibility to perform non-invasive in situ and operando analyses. X-ray tomography can be performed either in synchrotron or laboratory facilities and is particularly well-suited to analyze bulk materials and electrode/electrolyte interfaces. Several post Lithium-ion (Li-ion) devices, such as Li-sulfur, Li-O2, or all-solid-state Li batteries, have in common an anode made of metallic Li. The main failure mode of Li batteries is the inhomogeneity of the Li electrodeposits onto the Li anode during charge steps leading to dendrite growth and low Coulombic efficiency. X-ray tomography is a powerful tool to study dendrites as it provides useful information about their locations, dynamics, and microstructures. Since X-rays and neutrons interact differently with matter, the corresponding imaging techniques are complementary. So far, the use of neutron tomography is scarcely reported for Li deposit analysis due to the difficulty to reach sufficient image resolution to capture the deposit microstructure, i.e. typically below 10-20 µm. In this work, we report, as a proof-of-concept, an in situ neutron tomography imaging of Li electrodeposits in a cycled Li symmetric cell at a 7.4 µm voxel size. This relatively high resolution is achieved thanks to the capability of the neutron imaging beamline. In addition, the high contrast of Li isotopes intrinsic to neutron is employed to capture the Li comprising the deposits. Indeed, the linear neutron attenuation coefficient of 6Li is 13 times higher than that of natural Li. The electrochemical cell comprises a natural Li electrode, a 6Li electrode, and a deuterated liquid electrolyte. The neutron tomographies are compared with X-ray tomography images of the same electrochemical cell acquired both at an X-ray synchrotron beamline and at a laboratory X-ray tomograph. Neutron tomography is shown to be compatible with in situ analysis and capable to capture the overall morphology of the Li deposits in good accordance with X-ray tomography analyses.